Improving or Disappearing: Firm-Level Adjustments to Minimum Wages in China - Florian Mayneris; Sandra Poncet; Tao Zhang (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
We here consider how Chinese firms react to higher minimum wages, exploiting the 2004 minimum-wage Reform in China. After this reform, we find that the wage costs for surviving firms that were more exposed to minimum-wage hikes rose, but also that their productivity significantly improved, allowing them to absorb the cost shock without any change in their profitability and with limited job losses. Our results are robust to pre-existing trend analysis and an IV strategy. However, the survival probability of the firms that were most exposed to minimum-wage hikes fell after the Reform. Firm-level productivity gains partly came from better inventory management and greater investment in capital, at the cost of a reduction in firm-level cash.
Keywords: 330